Targeting and reprogramming microglial phagocytosis of neutrophils by ginsenoside Rg1 nanovesicles promotes stroke recovery - Kaichao Hu; Junrui Ye; Pinglong Fan; Ruifang Zheng; Shasha Wang; Ye Peng; Yuan Ruan; Xu Yan; Zhao Zhang; Shifeng Chu; Naihong Chen (Bioactive Materials)
Stroke remains one of the leading causes of adult disability worldwide, with neovascularization is crucial for brain repair after stroke. However, neutrophil infiltration hinders effective neovascularization, necessitating timely clearance by microglia through phagocytosis. Unfortunately, microglial phagocytic function is often impaired by metabolic defects, hindering post-stroke recovery. Ginsenoside Rg1, derived from Panax ginseng, exhibits neuroprotective properties and regulates cellular metabolism in vitro but its therapeutic application is limited by poor brain penetration. Here, we present a targeted delivery system utilizing neutrophil-like cell membrane vesicles (NCM), prepared via nitrogen cavitation, to enhance Rg1 delivery to the brain. These biomimetic vesicles exploit the inherent targeting ability of neutrophil membranes to reach brain injury sites and are subsequently taken up by microglia. Our findings demonstrate that Rg1-loaded vesicles enhance microglial clearance of neutrophils, reduce neutrophil extracellular traps release, and mitigate tissue damage. These effects improve the post-stroke microenvironment, promote vascular remodeling, and ultimately contribute to functional recovery. This strategy highlights the potential of targeted reprogramming microglial cells to enhance their endogenous repair capabilities, offering a promising therapeutic avenue for ischemic stroke management.